(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, the authors study the influence the form of the smooth unloading-reloading function on the nonlinear solution characteristics of the recently developed smooth unloading-reloading (SUR) approach for nonlinear finite element simulation of quasi-brittle materials. The SUR method uses a target function and a smooth unloadingreloading function to compute an approximate tangent matrix with an incremental-iterative Newtown type solution scheme. The smooth unloading-reloading function has two main parameters p a and ν which affect the form of the SUR function. The study is illustrated using different values of the two main parameters of the SUR curve. A Mathcad code has been written to carry out the nonlinear finite element analysis of the numerical example presented in this paper.